2020
DOI: 10.3390/su12156071
|View full text |Cite
|
Sign up to set email alerts
|

Glazed Photovoltaic-thermal (PVT) Collectors for Domestic Hot Water Preparation in Multifamily Building

Abstract: Photovoltaic–thermal collector generates electrical and thermal energy simultaneously from the same area. In this paper performance analysis of a potentially very promising application of a glazed photovoltaic–thermal collector for domestic hot water preparation in multifamily building is presented. Solar system in multifamily building can be installed on the roof or integrated in the façade of the building. The aim of this simulation study is to show difference of thermal and electrical performance between fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The electrical efficiency does drop when the PV temperature is high. Combined peak efficiency for the PVT array is therefore about 80%, which is close to reported values for this type of system [24,30,31].…”
Section: Pvt Performancesupporting
confidence: 87%
See 1 more Smart Citation
“…The electrical efficiency does drop when the PV temperature is high. Combined peak efficiency for the PVT array is therefore about 80%, which is close to reported values for this type of system [24,30,31].…”
Section: Pvt Performancesupporting
confidence: 87%
“…The electrical efficiency does drop when the PV temperature is high. Combined peak efficiency for the PVT array is therefore about 80%, which is close to reported values for this type of system [24,30,31]. The thermal efficiency as defined by Equation (8) plotted in Figure 10, along with electrical efficiency as determined by Equation (11).…”
Section: Pvt Performancesupporting
confidence: 80%
“…Additionally, these systems are occasionally integrated with heat pumps and seasonal energy storage [21,22]. The findings in research paper [23] indicate that the PV/T collector can attain higher energy production and efficiency compared to conventional systems, particularly when integrated into building facades.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…The proposed 1.25 kW p system contributed to 14.95% and 27.48% of electrical and thermal energy generation, respectively, as shown in Figure 14. Pokorny et al [94] conducted an experimental and analytical investigation of a new concept of glazed PVT collector (encapsulation was done using polysiloxane gel) for a multifamily building with 45 flats and 100 occupants in three locations. Two different configurations were tested involving rooftop installation and façade integration, and the simulation study results are shown in Figure 15.…”
Section: Water-based Pvt Systemsmentioning
confidence: 99%
“…Figure15. Thermal and electric yield for all the alternatives in three locations (reprinted from[94], with permission from publisher).…”
mentioning
confidence: 99%